Baseline Choroidal Microvasculature Dropout as a Predictor of Subsequent Visual Field Progression in Open-angle Glaucoma. Issue 8 (August 2021) - Jo, Youn Hye; Shin, Joong Won; Song, Min Kyung; Won, Hun Jae; Kook, Michael S.
Abstract : Precis: Choroidal microvasculature dropout (CMvD) is an independent predictor for overall and central visual field (VF) progression in open-angle glaucoma (OAG) eyes. Purpose: The purpose of this study was to investigate the impact of CMvD identified by optical coherence tomography angiography (OCT-A) at baseline on subsequent VF progression in eyes with OAG. Methods: This retrospective observational study included 80 OAG eyes with CMvD [CMvD(+)] and without CMvD [(CMvD(−)] at baseline [40 of each matched for both age (10 y and below) and baseline VF severity (⩽1 dB)]. The patients were followed regularly at 6-month intervals. VF progression was defined according to the Early Manifest Glaucoma Trial criteria. Associations of overall VF progression with baseline clinical factors, including the presence of CMvD and other variables, were analyzed by logistic regression with a generalized estimating equation in the entire OAG cohort. Linear mixed models were used to determine the differences in visual field mean sensitivity (VFMS) between the CMvD(+) and CMvD(−) groups globally and regionally at each follow-up point. Results: During a mean follow-up of 35.91±2.51 months, a significant difference was evident in the VF progression rate between the CMvD(−) and CMvD(+) groups (22.5% vs. 70%, P <0.001). CMvD at baseline and a higher visit-to-visit intraocular pressure fluctuation were significant predictors of VF progression. The VFMS differed significantly between the 2 groups at the central and superior central VF regions after 2 years of follow-up. Conclusion: The presence of CMvD at baseline is an independent predictor of subsequent VF progression. CMvD(+) eyes show a faster rate of VFMS loss at the central and superior central VF regions.